Cortical and cervical stimulation after hemispheric infarction. Issue 7 (July 1987) - Berardelli, A; Inghilleri, M; Manfredi, M; Zamponi, A; Cecconi, V; Dolce, G
Abstract : Cortical and cervical stimulation has been performed in 20 patients with hemiparesis or hemiplegia due to hemispheric infarction and in 20 control subjects. The motor action potentials (MAPs) were recorded from biceps and thenar muscles. MAPs evoked by stimulation of the undamaged hemisphere were normal in 18 out of 20 patients and in two there was a slight increase of central conduction time (CCT). The stimulation of the motor cortex of the damaged hemisphere did not evoke any response in 15 patients; in two the MAPs were absent in one muscle and in the remaining three were delayed in one or both muscles. Cervical MAPs were normal in 18 patients and delayed in the thenar muscle in two patients.